ISOLASI DAN SELEKSI CENDAWAN ENDOFIT DARI TANAMAN BETADIN (Jatropha multifida L.) DAN POTENSINYA SEBAGAI ANTIMIKROBA - Harahap, Israwati; Elsie, -; Nurjanah, Indri (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2017)
This research aimed to isolate and select endophytic fungi that potentially as antimicrobial from betadin plants (Jatropha multifida L.). Isolation of endophytic fungi was carried out using surface sterilization and selection of endophytic fungi using well diffusion method. A total of 13 isolates of endophytic fungi were obtained from J. multifida L. From a total of 13 isolates, 11 isolates were able to inhibit the growth of Candida albicans, 11 isolate was able to inhibit the growth of Staphylococcus aureus and 10 isolates were able to inhibit the growth of Escherichia coli.